2021
DOI: 10.32859/era.21.23.1-12
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal uses of plants by traditional birth attendants to facilitate childbirth among Djimini women in Dabakala (Center-North of Côte d'Ivoire)

Abstract: Background: Today, due to the still high rates of maternal death and incessant caesareans, the high cost of pharmaceutical drugs, parturients are turning to traditional midwives to facilitate childbirth. The purpose of this study is to identify and document the medicinal plants traditionally used for their oxytocic effect by the traditional midwives in the department of Dabakala.Methods: an ethnobotanical survey was conducted with 71 traditional midwives from the department of Dabakala. The data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…This education could promote the adoption of good practices in storing and delivering commercialized medicinal plants. On the other hand, previous studies conducted in other regions of Côte d'Ivoire by Gnagne et al (2017), Sidio et al (2020), and Koman et al (2021) show that this activity is practiced mostly by uneducated people.…”
Section: Discussionmentioning
confidence: 75%
“…This education could promote the adoption of good practices in storing and delivering commercialized medicinal plants. On the other hand, previous studies conducted in other regions of Côte d'Ivoire by Gnagne et al (2017), Sidio et al (2020), and Koman et al (2021) show that this activity is practiced mostly by uneducated people.…”
Section: Discussionmentioning
confidence: 75%
“…They serve a multitude of purposes, such as preventing miscarriages, alleviating abdominal discomfort, morning sickness, and swelling of extremities during pregnancy (Abdillahi & Van Staden 2013). Moreover, these plants are employed during labor to stimulate contractions and facilitate the expulsion of retained placentas (De Boer & Lamxay 2009, Koman et al 2021. Postpartum, medicinal plants are used as purgatives to cleanse the womb, stimulate lactation, reduce postpartum haemorrhage, and alleviate abdominal pains (Abdillahi & Van Staden 2013, Khadim et al 2023.…”
Section: Introductionmentioning
confidence: 99%
“…This species grows only in the undergrowth of the tropical forests and savannahs where it is used to treat amenorrhea and as uterotonic [9] [10]. Previous phytochemical studies realized on the essential oils of its stem barks revealed the presence of γ-terpinene, β-caryophyllene and germacrene D as major components [2].…”
Section: Introductionmentioning
confidence: 99%